Adaptation to implied tilt: extensive spatial extrapolation of orientation gradients - Roach, Neil; Webb, Ben (Frontiers in Psychology, 2013)
To extract the global structure of an image, the visual system must integrate local orientation estimates across space. Progress is being made towards understanding this integration process, but very little is known about whether the presence of structure exerts a reciprocal influence on local orientation coding. We have previously shown that adaptation to patterns containing circular or radial structure induces tilt-aftereffects (TAEs), even in locations where the adapting pattern was occluded. These spatially ‘remote’ TAEs have novel tuning properties and behave in a manner consistent with adaptation to the local orientation implied by the circular structure (but not physically present) at a given test location. Here, by manipulating the spatial distribution of local elements in noisy circular textures, we demonstrate that remote TAEs are driven by the extrapolation of orientation structure over remarkably large regions of visual space (more than 20 degrees). We further show that these effects are not specific to adapting stimuli with polar orientation structure (i.e. circular, radial), but require a gradient of orientation change across space. Our results suggest that mechanisms of visual adaptation exploit orientation gradients to predict the local pattern content of unfilled regions of space.